The Development of Japanese New Religions in Brazil and Their Propagation in a Foreign Culture - Watanabe, Masako (Japanese journal of religious studies, 2008)
This article will examine Ōmoto, Konkōkyō, and Risshō Kōseikai as examples of New Religions among Brazilians of Japanese descent, and Sekai Kyūseikyō, Sōka Gakkai, and Reiyūkai as Japanese new religions that have expanded through propagation to Brazilians of a non-Japanese ethnic background. It will examine the spread of Japanese new religions in the new cultural environment of Brazil, which factors caused the movements to remain only among Japanese-Brazilians, and which factors caused the movements to spread to non-ethnic-Japanese communities. The article will also look at the phenomenon of many Brazilians of Japanese descent who came to work in Japan in the 1990s, and the large impact that has had on Japanese new religions with regard to organizational restructuring. It will also look at how this was a new development for the religions of the ethnic Japanese community in Brazil, and as an opportunity for propagation among Brazilians of non-Japanese ethnic background.